Arteriovenous access banding revisited. Issue 3 (May 2017) - Teixeira, Gabriela; Almeida, Paulo; Sousa, Clemente N.; Teles, Paulo; De Sousa, Paulo; Loureiro, Luís; Teixeira, Sérgio; Rego, Duarte; Almeida, Rui; Norton de Matos, António
Purpose: The aim of this study is to validate the current applicability of arteriovenous access banding in high flow access (HFA) and/or haemodialysis access-induced distal ischaemia (HAIDI). Methods: This retrospective study was conducted at the GEV (Grupo de Estudos Vasculares) vascular access centre. The clinical records of consecutive patients undergoing banding for HAIDI and HFA symptoms, between June 2011 and January 2015, were reviewed until April 2015. All vascular access patients' consultation records and surgical notes were reviewed. We analysed and compared patients' age, gender, comorbidities, symptoms and intraoperative ultrasound control. We defined technical failure as recurrence of symptoms, requiring new banding. Excessive banding, access thrombosis, rupture and false aneurysm development were registered as complications. Primary clinical success was defined as improvement of symptoms or effective flow reduction after banding, with no need for reintervention. If one reintervention was necessary, we have defined it as secondary clinical success. Results: Overall, 119 patients underwent banding: 64 (54%) with HAIDI and 55 (46%) with HFA. The HAIDI group was significantly older (65 ± 13 years compared with 56 ± 22 years, p = 0.001) and had significantly greater number of patients with diabetes (56% vs 24%, p = 0.004). Primary success was achieved in 85 patients (71.4%) and the secondary success rate was 84.9%. Older age (p = 0.016) and intraoperative ultrasound control (p = 0.012) were significantly associated with primary success. Conclusions: Our results do not corroborate the high incidence of thrombosis previously reported as associated with AV access banding and suggest that ultrasound control is crucial for preventing technical failure. The procedure was effective on both compared groups.